Nature- Based solutions to support the ecosystem of sewri mangrove - Mitra, Rangeet (IIPA Digest)
According to Clough(2013), Tomlinson (1986), "Mangrove forest are trees, shrubs and ferns that occupy the inter- tidal areas between land and sea of tropical and subtropical regions." Because oftheir great capacity to trap carbon dioxide, they rank among the most productive ecosystem and contribute significantly in reducing the amount of carbon dioxide in the atmosphere. Mangroves span around 1,37,760km throughout the globe, with approximately 3.5% of the total area- 4921km- occupying India. With an area of 304 km, the Indian state of Maharashtra provides 6.2% of the country's total mangrove cover. Mangroves cover 66km square along the Mumbai shoreline. - Reproduced